2021
DOI: 10.3346/jkms.2021.36.e187
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Neurological Outcomes in Out-of-hospital Cardiac Arrest Survivors Immediately after Return of Spontaneous Circulation: Ensemble Technique with Four Machine Learning Models

Abstract: Background We performed this study to establish a prediction model for 1-year neurological outcomes in out-of-hospital cardiac arrest (OHCA) patients who achieved return of spontaneous circulation (ROSC) immediately after ROSC using machine learning methods. Methods We performed a retrospective analysis of an OHCA survivor registry. Patients aged ≥ 18 years were included. Study participants who had registered between March 31, 2013 and December 31, 2018 were divided int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 22 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…A lot of variables were reported to correlate with mortality in CA patients, such as hypertension, DM, the use of vasopressor. (32,(48)(49)(50) Nevertheless, our study showed that hypertension, DM and the use of epinephrine and dopamine were not predictors of in-hospital mortality of ICU admitted CA patients, which may be attribute to our relatively small sample size, and the difference in amount and duration of use vasopressors.…”
Section: Discussionmentioning
confidence: 60%
“…A lot of variables were reported to correlate with mortality in CA patients, such as hypertension, DM, the use of vasopressor. (32,(48)(49)(50) Nevertheless, our study showed that hypertension, DM and the use of epinephrine and dopamine were not predictors of in-hospital mortality of ICU admitted CA patients, which may be attribute to our relatively small sample size, and the difference in amount and duration of use vasopressors.…”
Section: Discussionmentioning
confidence: 60%
“…A lot of variables were reported to correlate with mortality in CA patients, such as hypertension, DM, the use of vasopressor [ 13 , 40 , 55 , 56 ]. Nevertheless, our study showed that hypertension, DM and the use of epinephrine and dopamine were not predictors of in-hospital mortality of ICU-admitted CA patients, which may be attributed to our relatively small sample size, and the difference in amount and duration of use vasopressors.…”
Section: Discussionmentioning
confidence: 99%